MUSHROOMING JOBSITES STRIKE ENDANGER TO JOBSEEKERS’ LIVES – JOBSBEE A FAKE JOBSITE – A TRUE CASE STUDY. - Dr. M E Purushoththaman (International Journal of Research Science and Management, 2018)
Some decades ago, for long years people had a Central / District Employment Office in each district(mostly), registered their names and other particulars, awaiting for their turn of call from those government run offices. Physical communication was made through hard copies after identifying the eligible candidate to call for interview and other processes which was time consuming and tedious to get a government job. Mostly private jobs are provided or arranged through references in their circles. It was the scenario before the introduction of private employment offices. The usage and growth of Internet and Computers and their related fields like software and hardware, forced to have private job providers to setup their offices with the permission of the government to reduce the burden. From the last decade of the 20 century onwards the growth of private companies and hence the requirement of recruiters, HR managers and the private job seekers are grown in virtue with the technology change. The physical setup slowly turned to online to fasten the process and hence the results. Problem was not so great till this point.